Pengaruh Fundamental Makro Dan Struktur Kepemilikan Terhadap Business Sustainability Dengan Green Accounting, Kinerja Keuangan, Dan Limbah Industri Sebagai Variabel Intervening Pada Perusahaan Energi Yang Terdaftar Di Bursa Efek Indonesia - Jofanka, Alinda Dwi; Hwihanus (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The focus of this research is to examine the influence of macro fundamentals and ownership structure on business sustainability with intervening variables in the form of green accounting, financial performance and industrial waste in energy companies listed on the Indonesia Stock Exchange. Data sourced from complete documents from 14 energy companies for 2021-2023 were analyzed using SmartPLS-based quantitative methods. The research results show that macro fundamentals have a significant effect on business sustainability and financial performance, but not on green accounting and ownership structure. Ownership structure has a significant effect on business sustainability, green accounting, financial performance and industrial waste. Green Accounting has a significant effect on business sustainability and financial performance, while financial performance is not significant on business sustainability. Industrial waste has a significant effect on business sustainability and financial performance.